Finite Element Analysis of Steel-Polypropylene Hybrid Fiber Concrete Penstock - HE Shan; WU Hailin; SI Dongdong (Renmin Zhujiang)
In order to improve the bearing capacity of steel-lined reinforced concrete penstock and ensure the safety and durability of the penstock, it is planned to mix hybrid fibers into the wrapped concrete of penstock for crack control. The steel fiber volume fraction is 0.5%, 1.0%, 1.5%, and the polypropylene fiber volume fraction is 0.05%, 0.10%, 0.15%. After mixing the steel fiber and polypropylene fiber, this paper simulates the damage process of steel-polypropylene hybrid fiber concrete penstock under internal water pressure through ABAQUS (as a finite element software) by the plastic damage model of concrete. The results show that the mixture of steel-polypropylene hybrid fiber can not only limit the crack development on wrapped concrete of penstock, but also reduce the crack load of penstock, and the stress of the steel also decreases with the increase of the volume fraction of the hybrid fiber.